2014
DOI: 10.1111/codi.12488
|View full text |Cite
|
Sign up to set email alerts
|

Self‐expandable metal stents in the treatment of benign anastomotic stricture after rectal resection for cancer

Abstract: Self-expandable metal stents represent a valid alternative to balloon dilatation to treat patients with benign symptomatic anastomotic stricture after colorectal resection for cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 25 publications
0
25
0
2
Order By: Relevance
“…Especially when a stricture is located in the rectum, it may cause severe symptoms, for which several therapeutic options are available: endoscopic balloon dilation (EBD) [2], placement of a self-expandable metal stent [3], revisional surgery, and palliative colostomy. However, the best treatment has yet to be determined.…”
mentioning
confidence: 99%
“…Especially when a stricture is located in the rectum, it may cause severe symptoms, for which several therapeutic options are available: endoscopic balloon dilation (EBD) [2], placement of a self-expandable metal stent [3], revisional surgery, and palliative colostomy. However, the best treatment has yet to be determined.…”
mentioning
confidence: 99%
“…Conventional approaches involve antibiotics, bowel rest, percutaneous drainage of collections and surgical drainage with stoma creation in the context of excessive peritoneal contamination [17]. An increasing number of reports indicate the efficacy of self-expandable metallic stents in the treatment of malign and benign obstructive colorectal diseases and postoperative fistulas [18][19][20][21]. DiMaio et al [10] concluded after their small case series that they had an 80% stenting success rate following lower digestive tract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, SEMS and balloon dilatation were used to complement each other. However, stents are prone to migration, pressure necrosis, perforation and bleeding, and when placed in the distal rectum they may not be tolerated by the patient [2]. Baatrup et al [8] have reported management of six cases of rectal stricture by transanal endoscopic microsurgery (TEM).…”
Section: Discussionmentioning
confidence: 99%